Return of the Eurasian lynx: using local stakeholder knowledge and experiences to inform lynx conservation in the French Alps - Justine Shanti Alexander; Philippe Christe; Fridolin Zimmermann (Oryx)
Large carnivore conservation in human-dominated landscapes is a complex issue, often marked by the stark contrast between those who hold deep-rooted animosity towards these animals and those who welcome their presence. The survival of the Eurasian lynx Lynx lynx in Europe relies on effective coexistence with humans in multi-use areas. We explored the experiences and perceptions of local hunters and pastoralists regarding the return of the lynx to the Giffre Valley, France, and mapped lynx distribution based on the probability of site use while accounting for detection probability. We conducted in-depth interviews with 29 respondents to gather data on lynx sightings, rationale for hunting and pastoralism, and perceptions of lynxes. We found that 45% of respondents had detected lynxes in the last 40 years, with an estimated site use of 0.66 ± SE 0.33 over the last decade, indicating there was a 66% probability of lynxes using the sites during that time period. Our results suggest that hunting and pastoralism in the region are rooted in a desire to carry on local traditions and connect with the natural world. Respondents generally tolerated the presence of lynxes, perceiving few threats to their livelihoods and activities, and expressing a willingness to coexist peacefully. However, some identified future challenges that could arise with the return of large carnivores to the valley and highlighted scenarios that could lead to a decline in tolerance. This study emphasizes the valuable knowledge of local hunters and pastoralists and their potential role in lynx population monitoring and conservation. Integrating stakeholder values in decision-making processes is crucial for inclusive and sustainable responses to promote biodiversity.